Homoseksualitas dalam Lagu-lagu Prancis - Tjahjani, Joesana (UI Scholars Hub, 2004)
Sexual revolution in France in the decade of the 1970s is characterized by social openness toward sex. There is a change in the pattern of spousal living, including same-sex relation. Homosexuals in France have the courage to declare their sexual orientation. Despite pros and cons within the French society, PACS or the solidarity civil pact, since 1999, allowed homosexual pairs to formalize their commitment outside marriage. French songs with homosexual themes began to appear in the decade of the 1960s. Since then, around 90 songs foreground homosexuality through various themes and perspectives. In the first reading, the lyrics only foreground the emergence of consciousness or confession of a homosexual. The theme of the orientation of homosexual behaviour can be found in most of the songs. Other themes are related to other perspectives. Further discussion shows that these songs are presented in terms of three negative perspectives: negative, positive and neutral. The negative perspective uses homosexuality as an object of joke, the second proposes defense for the homosexual community, and the neutral perspective is completely descriptive and generally portrays sexuality and sensuality among the homosexuals.